Dealing with Variability in Context-Aware Mobile Software - Fortier, Andrés (2010)
Mobile context-aware software pose a set of challenging requirements to developers as these applications exhibit novel features, such as handling varied sensing devices and dynamically adapting to the user’s context (e.g. his or her location), and evolve quickly according to technological advances. In this paper, we discuss how to handle variability both across different domains and during the evolution of a single application. We present a set of design structures for solving different problems related with mobility (such as location sensing, behaviour adaptation, etc.), together with the design rationale underlying them, and show how these sound micro-architectural constructs impact on variability. Our presentation is illustrated with case studies in different domains.